2012
DOI: 10.2478/v10032-012-0014-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cultivar and Biostimulant Treatment on the Carrot Yield and its Quality

Abstract: Summary Modifications in growing techniques can affect the yield and nutritional quality of various cultivated plants. Among them, the use of biostimulants is environmental friendly method of stimulating crop productivity, stress resistance, and affecting yield or chemical composition of the plants. The aim of the investigation was determining of the effect of biostimulant treatment on yield and its quality of carrot grown for summer harvest. The experiment was carried out in 2009-2011 in the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
33
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 7 publications
(7 reference statements)
6
33
0
3
Order By: Relevance
“…Aminoplant influenced yield of roots and leaf rosette mass, increased the soluble sugars content in carrot roots and affected dry matter content. A significant effect of Aminoplant on nitrate content was also observed, but the results were not repeatable in the experimental years, so different climatic conditions may have modified carrot response (Grabowska et al 2012). In general, different crops treated with this biostimulant had greater yields per hectare (Maini 2006).…”
Section: Application Of Biostimulants On Vegetable Cropsmentioning
confidence: 93%
“…Aminoplant influenced yield of roots and leaf rosette mass, increased the soluble sugars content in carrot roots and affected dry matter content. A significant effect of Aminoplant on nitrate content was also observed, but the results were not repeatable in the experimental years, so different climatic conditions may have modified carrot response (Grabowska et al 2012). In general, different crops treated with this biostimulant had greater yields per hectare (Maini 2006).…”
Section: Application Of Biostimulants On Vegetable Cropsmentioning
confidence: 93%
“…Papaya (Carica papaya) yields were increased by 22 % when plants were sprayed at monthly intervals with Siapton (Morales-Payan and Stall 2003). (Kunicki et al 2010) and Gajc-Wolska et al (2012) found no effect of Aminoplant (Siapton) on yield of spinach (Spinacia oleracea) and endive (Chicorium pumilum), respectively, in field trials and (Grabowska et al 2012) showed an effect on carrot (Daucus carota) yield only for one variety in one year of three years of field trials and soluble sugars and carotenoids increased and nitrate content decreased in Aminoplant-treated carrot roots relative to the control in one year of two field trials. An alfalfa hydrolysate increased leaf growth, foliar sugar content and decreased nitrate content of hydroponically-grown maize plants (Schiavon et al 2008) and in more recent studies, enhanced short-term growth of hydroponically-grown maize in the absence and presence of salt stress (NaCl) (Ertani et al 2013b).…”
Section: Specific Effects Of Protein Hydrolysates and Amino Acids On mentioning
confidence: 98%
“…Protein hydrolysates are prepared by enzymatic, chemical or thermal hydrolysis of a variety of animal and plant residues, including animal epithelial or connective tissues (Cavani et al 2006;Ertani et al 2009Ertani et al , 2013aGrabowska et al 2012;Kauffman et al 2007;Kunicki et al 2010;Maini 2006;Morales-Payan and Stall 2003), animal collagen and elastine (Cavani et al 2006), carob germ protein (Parrado et al 2008), alfalfa residue (Schiavon et al 2008;Ertani et al 2009Ertani et al , 2013b, wheat-condensed distiller solubles (García-Martínez et al 2010 Protein/peptide and free amino acid contents of the hydrolysates vary in these preparations in the range of 1-85 % (w/w) and 2-18 % (w/w), respectively. The major amino acids include alanine, arginine, glycine, proline, glutamate, glutamine, valine and leucine (Parrado et al 2008;Ertani et al 2009;García-Martínez et al 2010).…”
Section: Protein Hydrolysates and Amino Acidsmentioning
confidence: 99%
“…2), indicating that the use of foliar fertilizers could possibly attenuate the stress caused by metribuzin. It is known that temperature influences plant metabolism, and different climatic conditions can modify the reaction of carrot plants to the application of biostimulants (Grabowska et al, 2012).…”
Section: Resultsmentioning
confidence: 99%